Study on Place of Women In the Indian Society and Views of College Girls a Case Study: Exploring Gender Perceptions and Progress of Women in Contemporary Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2011)
We tried toexplore the college girls’ perceptions of their gender being considered as‘weaker sex’ in the contemporary India society. As many as 80 per cent indeedbelieved that they are still the weaker sex, although 89.25 per cent of therespondents believed that the modern Indian women are equally capable,efficient and committed to take up any, skilled job in any walk of life. A vastmajority of the respondents (about 70 per cent) believe that despite all theloud propaganda about the women’s uplift and progress in India, our women, byand large, are not getting their due recognition and fair treatment from theIndian state and the society. They (as many as 73 per cent respondents)believed that due to their lack of knowledge about the legal provisions fortheir protection and upholding their dignity as human being, they are stillbeing subjected to injustices and are suffering from helplessness andalienation. The fact that although the bill for reservation of seats for womenin the Parliament was passed in the 13th Lok Sabha, it is not likely to beeffective as some political parties are putting spanner in the wheel in thename of reservations for OBCs and other separately.